2020
DOI: 10.1001/jamahealthforum.2020.0718
|View full text |Cite
|
Sign up to set email alerts
|

Will Medicare’s New Patient-Driven Postacute Care Payment System Be a Step Forward?

Abstract: Skilled nursing facility (SNF) and home health agency (HHA) use and spending vary substantially across the US. However, higher spending on rehabilitation and nursing following a hospitalization has not necessarily led to better patient outcomes. 1 In 2017, approximately 1.6 million patients receiving Medicare fee-for-service benefits were admitted to a SNF, with an estimated annual cost of $28.4 billion, and 3.4 million patients received HHA services at a cost of $17.7 billion. 2 Consequently, SNFs and HHAs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Instead, they are determined by patients' clinical and functional characteristics at the time of their SNF admission. 6 Previous research has demonstrated that these altered incentives resulted in modest cuts in therapy staffing levels by SNFs during the first quarter of program implementation. 7 However, the association between the PDPM and the amount and type of therapy delivered to Medicare SNF patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they are determined by patients' clinical and functional characteristics at the time of their SNF admission. 6 Previous research has demonstrated that these altered incentives resulted in modest cuts in therapy staffing levels by SNFs during the first quarter of program implementation. 7 However, the association between the PDPM and the amount and type of therapy delivered to Medicare SNF patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…6 PDGM also shortens the payment period from 60 days to 30 days and the expected number of therapy visits is no longer considered in the payment calculation. 6 Additionally, the payment rate is reduced after the first 30-day period. 6 These features of the PDGM have potentially important implications for medically complex patients who may require longer home health stays or a greater number of home health visits before being discharged to the community.…”
Section: Introductionmentioning
confidence: 99%
“…The PDGM was designed to place greater emphasis on a patient's clinical, health, and functional characteristics when determining the payment rate 6 . PDGM also shortens the payment period from 60 days to 30 days and the expected number of therapy visits is no longer considered in the payment calculation 6 . Additionally, the payment rate is reduced after the first 30‐day period 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations